2013
DOI: 10.1109/tsp.2012.2232660
|View full text |Cite
|
Sign up to set email alerts
|

Gain-Constrained Recursive Filtering With Stochastic Nonlinearities and Probabilistic Sensor Delays

Abstract: Abstract-This paper is concerned with the gainconstrained recursive filtering problem for a class of timevarying nonlinear stochastic systems with probabilistic sensor delays and correlated noises. The stochastic nonlinearities are described by statistical means that cover the multiplicative stochastic disturbances as a special case. The phenomenon of probabilistic sensor delays is modeled by introducing a diagonal matrix composed of Bernoulli distributed random variables taking values of 1 or 0, which means t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 36 publications
0
77
0
Order By: Relevance
“…Finally, an example has been given to illustrate the usefulness of the developed state estimation approach. The results in this paper could be further extended to the non-fragile state estimation problems for discrete neural networks with more complicated networkinduced phenomena such as fading measurements [4], [5], [10], [20], [26], missing measurements [8], sensor delays [9], randomly occurring faults [14] and mixed time-delays [31].…”
Section: Discussionmentioning
confidence: 91%
“…Finally, an example has been given to illustrate the usefulness of the developed state estimation approach. The results in this paper could be further extended to the non-fragile state estimation problems for discrete neural networks with more complicated networkinduced phenomena such as fading measurements [4], [5], [10], [20], [26], missing measurements [8], sensor delays [9], randomly occurring faults [14] and mixed time-delays [31].…”
Section: Discussionmentioning
confidence: 91%
“…It is well recognized that the existence of the randomly occurring incomplete information would highly degrade the system performance if not handled properly. So far, a series of estimation and filtering schemes has been developed for networked systems with randomly occurring incomplete information in the literature, and great efforts have been made to deal with the randomly occurring nonlinearities in [49], [95]- [99], the randomly occurring uncertainties in [94], [97], the randomly occurring sensor saturations in [40], [72], the randomly occurring sensor delays in [31], [32], [38], [100], [101], the randomly occurring signal quantization in [41], [102], and the randomly occurring faults in [103]. Accordingly, several techniques for analysis and synthesis of the networked systems have been given, including innovation analysis approach [31], [32], linear matrix inequality approach [97], Hamilton-Jacobi-Isaacs inequality method [100], difference linear matrix inequality method [41], Riccati difference equation approach [101], [102], and game theory method [54].…”
Section: E Randomly Occurring Incomplete Informationmentioning
confidence: 99%
“…The filtering problems for networked systems with stochastic nonlinearities have already stirred some research interests and some latest results can be found in [16], [43], [45], [52], [101] based on several analysis techniques. For example, by using the Riccati-like difference equation approach, the extended Kalman filter has been designed in [16] for a class of time-varying networked systems with stochastic nonlinearities and multiple missing measurements.…”
Section: B Nonlinear Networked Systemsmentioning
confidence: 99%
See 2 more Smart Citations